2020
DOI: 10.1039/c9nr09781c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of catalyst-assisted growth of nonpolar GaN nanowiresviaa modified HVPE process

Abstract: Catalyst-assisted nonpolar GaN nanowires with a triangular cross section have been synthesized using a modified HVPE process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It is mainly attributed to be the formation of a rich surface state and oxygen defect levels of the assynthesized 2D GaN crystal, which suppresses the radiative recombination of photogenerated electrons and holes near the band edge. 32 The optoelectronic properties of the 2D GaN crystal were further investigated by a fabricated prototypical device, as shown in Figure S10a. The characteristic I−V curve under the dark condition (Figure S10b) also reveals that the 2D GaN crystal has a high dark current and carrier concentration caused by the shallow donor levels of defects, as depicted from the PL spectrum.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is mainly attributed to be the formation of a rich surface state and oxygen defect levels of the assynthesized 2D GaN crystal, which suppresses the radiative recombination of photogenerated electrons and holes near the band edge. 32 The optoelectronic properties of the 2D GaN crystal were further investigated by a fabricated prototypical device, as shown in Figure S10a. The characteristic I−V curve under the dark condition (Figure S10b) also reveals that the 2D GaN crystal has a high dark current and carrier concentration caused by the shallow donor levels of defects, as depicted from the PL spectrum.…”
Section: Resultsmentioning
confidence: 96%
“…Instead, the intrinsic band edge emission peak at 365 nm is not observed. It is mainly attributed to be the formation of a rich surface state and oxygen defect levels of the as-synthesized 2D GaN crystal, which suppresses the radiative recombination of photogenerated electrons and holes near the band edge . The optoelectronic properties of the 2D GaN crystal were further investigated by a fabricated prototypical device, as shown in Figure S10a.…”
Section: Resultsmentioning
confidence: 99%
“…These metallic particles may result in the formation of unavoidable defects and thus lead to negative effects on optical and electronic properties of the as-grown nanowires, which has been proven by several research groups. [87][88][89][90][91] For example, Karakostas et al compared GaN nanowires grown by either catalyst-free or catalyst-induced methods utilizing Ni seeds and found that the catalyst-induced nanowires contain many more basal-plane stacking faults and their photoluminescence is much weaker in comparison to that of the nanowires synthesized by the catalyst-free route (Figure 2i). [92] A more critical problem is the incorporation of metallic particles within nanowires that typically causes detrimental impacts on device performance.…”
Section: Synthesis and Growth Of Bottom-up Nanowiresmentioning
confidence: 99%
“…Ning et al clearly demonstrated the blue shift of UV emission, peak narrowing, and enhanced luminescence delay (350–390 nm spectral window) of a -axis GaN nanowires against c -axis GaN nanowires . We have also developed a modified hydride vapor phase epitaxy process to synthesize nonpolar GaN nanowires with a triangular cross section . Compared with the widespread study of c -axis polar GaN nanowires, nonpolar GaN nanowires are rarely reported due to their difficult synthesis. , To date, obtaining nonpolar GaN nanowires mainly relies on the complicated MOCVD process or the time-consuming cutting of c -axis GaN bulk crystals along its a / m plane. , Moreover, a foreign substrate is normally required for the nucleation and heteroepitaxial growth of polar/nonpolar GaN crystals, which also brings some stacking faults and structural strain due to their lattice mismatch .…”
Section: Introductionmentioning
confidence: 99%